Models for Cistercian Life in Jocelin of Furness's Vita Waldevi - Freeman, Elizabeth (Cistercian studies quarterly, 2002)
Focuses on the life of a Cistercian in the book 'Vita Waldevi,' by Jocelin of Furness. Emphasis on the life of Saint Walthoef, second abbot of the Cistercian abbey of Melrose in Scotland; Description of the youth and monastic life of Waltheof; Process of becoming a Cistercian monk.